The Influence of Leader Member Exchange Quality on Employee Performance through Intention to Quit Work - Jalius, Hendra; Salim, Agus (Dinasti Publisher, 2024)
The focus of this research is on PT Permodalan Nasional Madani Pekanbaru Branch Office, using independent variables consisting ofleader member exchange (LMX), the dependent variable is employee performance, and the intervening variable is the employee's intention to quit work. This research aims to analyze how big the influence of relationship quality isleader member exchange (LMX) on employee performance at PT Permodalan Nasional Madani Pekanbaru Branch Office with intention to quit work as an intervening variable. The sample consisted of 100 employees of AO PT Permodalan Nasional Madani Pekanbaru Branch Office and all employees were taken as samples using the census method. Research data was analyzed using the SmartPLS series 4 application. The data analyzed came from questionnaires distributed to all employees sampled in this research. Based on the research results, it can be concluded that the better the quality of LMX, the better the performance of employees at PT Permodalan Nasional Madani (PT PNM) Pekanbaru branch office. LMX quality does not significantly influence employee performance through intention to quit work as an intervening variable at PT Permodalan Nasional Madani (PT PNM) Pekanbaru branch office.